HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PENCEGAHAN HIV/AIDS DI KOMUNITAS REMAJA - Asriaty Dinopawe; Petriana E Mahmud; Arni Sabban (Pasapua Health Journal, 2022)
Introduction: Cases of HIV/AIDS infection which continue to increase, especially from the youth community, is a serious problem. lack of knowledge and attitudes of adolescents about HIV/AIDS can affect preventive actions against HIV/AIDS. This study aims to analyze the relationship between knowledge and attitudes of adolescents and prevention of HIV/AIDS in the youth community. Methods: This study used an analytic survey design with a cross sectional approach. A sample of 157 people was selected by purposive sampling technique. The statistical test used is the che squre test. Results: This study shows that there is a relationship between knowledge and HIV/ AIDS prevention in the youth community with a p value = 0.001 and there is a relationship between attitudes and HIV/AIDS prevention in the youth community with a p value = 0.000. Conclusion: Adolescent attitudes and knowledge about HIV/AIDS prevention can reduce the spread of the virus in a community.